2020
DOI: 10.1200/jco.19.01067
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and Late Complications of Hepatoblastomas Treated Using the Japanese Study Group for Pediatric Liver Tumor 2 Protocol

Abstract: PURPOSE We report here the outcomes and late effects of the Japanese Study Group for Pediatric Liver Tumors (JPLT)-2 protocol, on the basis of cisplatin-tetrahydropyranyl-adriamycin (CITA) with risk stratification according to the pretreatment extent of disease (PRETEXT) classification for hepatoblastoma (HB). PATIENTS AND METHODS From 1999 to 2012, 361 patients with untreated HB were enrolled. PRETEXT I/II patients were treated with up-front resection, followed by low-dose CITA (stratum 1) or received low-dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 31 publications
0
59
1
Order By: Relevance
“…However, a recent SIOPEL study showed that the OS rates of PRETEXT IV patients were increased from 61% in SIOPEL‐2 to 88% in SIOPEL‐4 4 . In addition, the JPLT‐2 trial showed an improved OS rate of 67% among patients with PRETEXT IV disease compared with 50.3% in the JPLT‐1 trial 5,22 . In the present study, survival outcomes were significantly associated with the PRETEXT stage in the early cohort but not in the late cohort.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…However, a recent SIOPEL study showed that the OS rates of PRETEXT IV patients were increased from 61% in SIOPEL‐2 to 88% in SIOPEL‐4 4 . In addition, the JPLT‐2 trial showed an improved OS rate of 67% among patients with PRETEXT IV disease compared with 50.3% in the JPLT‐1 trial 5,22 . In the present study, survival outcomes were significantly associated with the PRETEXT stage in the early cohort but not in the late cohort.…”
Section: Discussioncontrasting
confidence: 57%
“…PRETEXT staging at diagnosis is crucial for the risk stratification of patients with hepatoblastoma. Several trials have confirmed that the PRETEXT stage is a strong predictor of OS for patients with hepatoblastoma 5,10,11 . In the Intergroup CCG/POG study INT‐0098, the OS rates of patients with PRETEXT IV hepatoblastoma were as low as 30.9% 10 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to the COG risk stratification system, the CHIC risk stratification system excluded pathologic subtypes and included age at diagnosis to form stratification trees based on four clinically familiar PRETEXT groups. Over the past 10 years, four major organizations have been devoted to exploring effective prognostic factors in children with HB (23,24,(26)(27)(28)(29). In 2013, based on a database involving 1605 HB cases treated between 1988 and 2008 from eight completed HB trials, CHIC identified novel prognostic factors for HB (15).…”
Section: Discussionmentioning
confidence: 99%